(3eGdGjSY GdWHjH Lgdgs - (3jhSa Hf ESeGYjd Hf EdjGS Hf CMeO, CHh GdeMGSf, fUjQ GdOjf GdNhjj GdTGaYqj GdHZOGOj GdeYQha HGHf GdcJHj,J (B754 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3aEfg deG cGf GdEfSGf Hd GdMjhGf LedI ef GdeQcHGJ GdYfUQjI, hGdeJhdOGJ GdEeJRGLjI, Cf jchf OGFekG BNPkG aj GdPHhd hGdJNdd eJbdH GdCMhGd s
(3BNQgG (B:s
(3jeg(B: (3Se HGdeZQH dfHJg hQbgG jTHg hQb GdgfOjG EdG GfgG CUZQ hCeGSGb jNQL ef hSWgG hgj oeLQHI aj EdUGb GdLQGMGJ WQjI hjGHSI hGddg CYde Je gPG GdcJGH s
(3fSNI QGHYIs
(3hbO cJHJ YfGhjfgG HGdMeQI ade JXgQ ai GdJUhjQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B144s
Keywords: (3GdWHs